Evaluation of a National Care Coordination Program to Reduce Utilization Among High-cost, High-need Medicaid Beneficiaries With Diabetes. Issue 6 (June 2020) - Duru, O. Kenrik; Harwood, Jessica; Moin, Tannaz; Jackson, Nicholas J.; Ettner, Susan L.; Vasilyev, Arseniy; Mosley, David G.; O'Shea, Donna L.; Ho, Sam; Mangione, Carol M.
Abstract : Background: Medical, behavioral, and social determinants of health are each associated with high levels of emergency department (ED) visits and hospitalizations. Objective: The objective of this study was to evaluate a care coordination program designed to provide combined "whole-person care, " integrating medical, behavioral, and social support for high-cost, high-need Medicaid beneficiaries by targeting access barriers and social determinants. Research Design: Individual-level interrupted time series with a comparator group, using person-month as the unit of analysis. Subjects: A total of 42, 214 UnitedHealthcare Medicaid beneficiaries (194, 834 person-months) age 21 years or above with diabetes, with Temporary Assistance to Needy Families, Medicaid expansion, Supplemental Security Income without Medicare, or dual Medicaid/Medicare. Measures: Our outcome measures were any hospitalizations and any ED visits in a given month. Covariates of interest included an indicator for intervention versus comparator group and indicator and spline variables measuring changes in an outcome's time trend after program enrollment. Results: Overall, 6 of the 8 examined comparisons were not statistically significant. Among Supplemental Security Income beneficiaries, we observed a larger projected decrease in ED visit risk among the intervention sample versus the comparator sample at 12 months postenrollment (difference-in-difference: −6.6%; 95% confidence interval: −11.2%, −2.1%). Among expansion beneficiaries, we observed a greater decrease in hospitalization risk among the intervention sample versus the comparator sample at 12 months postenrollment (difference-in-difference: −5.8%; 95% confidence interval: −11.4%, −0.2%). Conclusion: A care coordination program designed to reduce utilization among high-cost, high-need Medicaid beneficiaries was associated with fewer ED visits and hospitalizations for patients with diabetes in selected Medicaid programs but not others. Abstract : Supplemental Digital Content is available in the text.